#### Answer

$4+1+(-2)+(-5)$
$-2$

#### Work Step by Step

$\sum_{i=1}^4(-3x_i-2)$
$=(-3x_1-2)+(-3x_2-2)+(-3x_3-2)+(-3x_4-2)$
$=(-3*(-2)-2)+(-3*(-1)-2)+(-3*0-2)+(-3*1-2)$
$=4+1+(-2)+(-5)$
$=\boxed{-2}$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$4+1+(-2)+(-5)$
$-2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.